BOOK REVIEW: Patocka J. & Turcani M.: Lepidoptera Pupae. Central European Species. Vol. I, II. - I. NOVÁK (European Journal of Entomology, 2007)
Apollo Books, Stenstrup, 2005, 542 + 321 pp. (271 Pls). ISBN 87-88757-47-1. Price DKK 960,00.